Investigation of the Operations of Open Pit Iron Mineralization for Acid Mine Drainage (Adana/Saimbeyli) - Ayşe Dokuzlar; Nil Yapıcı (Doğal Afetler ve Çevre Dergisi, 2021)
This study includes the field and laboratory studies (statics tests related to the Acid Production Potential [APP], Neutralization Potential [NP]) to investigate the estimation for the formation of Acid Mine Drainage of an iron mineralization located in Kaburluk, Saimbeyli District, Adana Province. An iron ore formation in the studied region is located in a trap in the dolomitic limestones of the middle Devonian at the base of the shale sandstone-limestone sequences of the upper Devonian. X-ray Fluoresence (XRF), X-ray Diffraction (XRD), total sulfur (S), NP, Net Neutralization Potential (NNP), Acid Production Potential (APP), mud pH and squirting tests were carried out on the ore and other rocks samples collected from the study area within in the scope of geochemical and static tests. The NP, Net Neutralization Potential (NNP), APP, Neutralization Potential Ratio (NPR=NP/APP) values of the samples were evaluated based on the data obtained. The paragenesis of the mineralization was composed of hematite, gothite siderite and limonite, while constitutes dolomite, calcite and pyrite minerals constitute the host rock. According to the results of the analysis performed on the host rocks, % total S: 0.21-0.42, NP (∑NP (kg/ton)): 289.07-478.07, APP sulfuric acid equivalents (kg / ton): 13, 13- 26.25 were determined. The NPR values were found to be between 11.01 -31.26. According to the results belonging to the ore samples, the following values were calculated: % total S: 0.03-0.09, NP (∑NP (kg / ton)): 8.07-53.16, APP sulfuric acid equivalents (kg / ton): 1.56- 5.56. The NPR values of the ore sample varied 2.58 and 16.50. According to the NPR values, there was no acid producing potential of the ore-bearing samples and host rocks. However, it is recommended that kinetics test should be performed after mining activities start in the region as there is a potential to generate acid during conducting mining operations.